The effects of pH on nutrient availability depend on both soils and plants - Barrow, N. J.; Hartemink, Alfred E. (Plant and soil, 2023)
The effects of pH on nutrient availability are not solely caused by to the effects on reaction with soils but are an interaction between these effects and the effects on rate of uptake by plants. Some effects are specific to particular ions, but an important aspect is that plant roots and soil particles both have variable charge surfaces. This influences availability, but in opposite directions. Sulfate is an example of this interplay. Its sorption by soil decreases markedly with increasing pH and thus “soil availability” increases. However, plant uptake also decreases with increasing pH thus “plant availability” decreases. For phosphate, the plant effect is stronger than the soil effect and uptake decreases with increasing pH. In contrast, effects of increasing pH on molybdate adsorption are so large that they dominate the overall effect. Sorption of cations, such as zinc or copper, increases with increasing pH but uptake rate also increases. The net effect is a small decrease in availability with increasing pH. Boron is an exception; there are small effects of pH on sorption; and it is the uncharged boric acid molecules that are taken up by plant roots. Their uptake is not affected by charge and uptake is proportional to the concentration of uncharged boric acid molecules. We argue that emphasis on the effects of pH on reactions with soil has led to a distorted picture of the effects of pH on nutrient availability.